The best science, the best science in Finnish – and English – or the best Finnish scientists? - David Hoffman; Thomas Babila Sama; Ahmad El-Massri; Mika Raunio; Marjaana Korhonen (Recherches en Éducation)
This article confronts an ‘uncomfortable truth’ or myth concerning the operationalization of equity-based personnel policy and practice in a higher education system one would expect to find it: Finland, a country widely admired for its relative lack of social stratification. This study is a participative inquiry by the authors, who draw on their collective experiences and perceptions from inside a rapidly changing system. Methodologically, the authors give voice – through the use of an approach generally ignored by higher education researchers in Finland – to a set of assertions about the system they work in and the mechanisms by which debate on equity concerning educational policy, in general and personnel practices, in particular, has faded from the policy agenda. The irony, of course, is that Finland’s greatest educational achievements rest on Nordic notions about precisely this topic. Finally, the implications of these dynamics are illuminated with regard to key (mis)understandings related to traditional internationalization efforts in higher education and migration-driven phenomena of a very different nature.